Mengembalikan Ide Dasar Keseimbangan Tujuan Pemidanaan: Koreksi atas Wacana Penerapan Restorative Justice Terhadap Tindak Pidana Korupsi - Fina Rosalina (Ajudikasi : Jurnal Ilmu Hukum, 2022)
Corruption has a systemic impact, giving birth to a paradigm of case settlement using the Comprehensive Extra Ordinary Measures method which is repressive. However, in its development, the mechanism is considered ineffective to apply. Restorative justice was born as a substitute discourse for repressive mechanisms. However, in the development of the concept of restorative justice, it is described as the abolition of sanctions for perpetrators of criminal acts of corruption by prioritizing the return of state financial losses. The normative juridical method is the method chosen to answer the formulation of the problem in the form of whether the discourse on the application of restorative justice for eradicating corruption has been in accordance with the basic idea of ​​​​balancing the goals of punishment in Indonesia. The results of the study found that, theoretically, the application of restorative justice has been in accordance with the direction of the goal of punishment which is monodualistic in nature (daad en dader straftrecht). The concept of restorative justice does not abolish the imposition of sanctions for perpetrators of corruption, either in the form of criminal or non-criminal sanctions. Theoretically, the imposition of sanctions is an effort to consider the balance between the interests of the community and the interests of individuals (daad en dader straftrecht).